The role of the Colombian farmers in the process of development of the country - Valbuena, Yuli Paola; Moreno, Diana Carolina; Restrepo, Deyanira (Rastros Rostros, 2011)
This article is based on the research work “Political proposals in the nine teenth century colombian novel” of Universidad Cooperativa de Colombia, Bucaramanga, 2009, that has been done in the past two years from the work La casa de las dos Palmas to raise a pedagogic proposal through the mainstreaming of Spanish and social studies for students in ninth grade of public schools in Bucaramanga. The book La casa de las dos Palmas written by Manuel Mejía Vallejo in the late twentieth century, relates country’s urbanization process lived in the colonization of Antioquia, which was similar to that experienced in other regions of country.